2022
DOI: 10.48550/arxiv.2203.04380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On finite time Type I singularities of the Kähler-Ricci flow on compact Kähler surfaces

Abstract: We show that the underlying complex manifold of a complete non-compact twodimensional shrinking gradient Kähler-Ricci soliton (M, g, X) with soliton metric g with bounded scalar curvature Rg whose soliton vector field X has an integral curve along which Rg → 0 is biholomorphic to either C × P 1 or to the blowup of this manifold at one point. Assuming the existence of such a soliton on this latter manifold, we show that it is toric and unique. We also identify the corresponding soliton vector field. Given these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Then there are two possibilities: either along each flow line, scalar curvature tends to zero, or there is a flow line along which scalar curvature tends to a positive number. Combining the curvature estimate (1.4) with Kähler condition, Cifarelli-Conlon-Deruelle [24] shows that the aforementioned dichotomy can be expressed as a simpler one: either lim This is proved by Conlon-Deruelle-Sun (cf. [25]).…”
Section: Propertiesmentioning
confidence: 89%
See 3 more Smart Citations
“…Then there are two possibilities: either along each flow line, scalar curvature tends to zero, or there is a flow line along which scalar curvature tends to a positive number. Combining the curvature estimate (1.4) with Kähler condition, Cifarelli-Conlon-Deruelle [24] shows that the aforementioned dichotomy can be expressed as a simpler one: either lim This is proved by Conlon-Deruelle-Sun (cf. [25]).…”
Section: Propertiesmentioning
confidence: 89%
“…This is finished in Cifarelli-Conlon-Deruelle [24] and Bamler-Cifarelli-Conlon-Deruelle [5]. In Cifarelli-Conlon-Deruelle [24], it is shown that M is biholomorphic to P 1 ×C or Bl 1 (P 1 ×C).…”
Section: Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The principal motivation behind Theorem A is that it provides a first step in the construction, via the continuity method, of a complete shrinking gradient Kähler-Ricci soliton with bounded scalar curvature on the blowup of C × P 1 at one point, a manifold identified in [CCD22, Conjecture 1.1] as a potential new example admitting such a soliton. As shown in [CCD22], a soliton on this manifold with bounded scalar curvature must be invariant under the standard torus action, and even though the conditions on the potential soliton vector field X of Theorem A are stringent, they are evidently true for the manifold in question as one can check in [CCD22,Example 2.32]. This example therefore fits into the framework of Theorem A, precisely with D = P 1 and π the blowup map.…”
mentioning
confidence: 84%